Presentation: Religiones y Espacio Andino - Romero Cevallos, Catalina Eugenia (2004)
In this issue of Allpanchis we collect some of the papers presented at the IX Congress of ALER (Latin American Association for the Study of Religions), which took place at the Pontifical Catholic University of Peru in 2002. The theme of the congress was "Religion and Ethnicity", with an emphasis on the Andean region, and was attended by researchers from Peru, Mexico, Argentina, Brazil, Colombia, Chile, the United States, Uruguay, among other Latin American and European countries.